A Comparative Study Between Frayer Model And Concept Mapping Strategy to Enhance Students’ Vocabulary Acquisition - Panjaitan, Nelson Balisar; Sihotang, Hana Monica (LPPM Universitas Advent Indonesia, 2020)
Abstract This study intends to find out what is the initial knowledge of the students before they were treated using Frayer Model and Concept Mapping Strategy, ascertain of the significant difference between these two teaching strategies, and to know the responses of the students after they were taught using Frayer Model and Concept Mapping Strategy are the aims of this research. This is a quantitative study with comparative design to know the students’ vocabulary acquisition test. The research instrument of this study is pre-and-post-test. This study was conducted among eleventh grader students at SMAN 1 Parongpong. The results of this study showed that the initial score for both respondents are quite similar with the score for FM group which is 30.50 and for CMS group which is 33.40. It is also known that there is a significant difference in students’ vocabulary acquisition between students who are taught with Frayer Model and those who are taught with Concept Mapping Strategy showed by the result of the mean differences from both groups are 0.000 < 0.05. The questionnaire’s result also supports that both teaching strategies are eligible to be applied in teaching active and passive voice construction with the score for FM class which is 55% and for the CMS class which is 80%, it can be categorized as “Good”. It implies that the implementation of Frayer Model and Concept Mapping Strategy enhances student’s vocabulary acquisition. Keywords: Language Proficiency, Vocabulary Acquisition, Frayer Model, Concept Mapping Strategy